Reaksi Pasar atas Pelaksanaan Serah Terima Presidensi Group of Twenty (G20) Indonesia - Kusuma, I Gusti Ayu Agung Kadek Rheina; Yasa, Gerianta Wirawan (Fakultas Ekonomi Universitas Samudra, 2024)
On 30-31 October 2021 the Group of Twenty (G20) carried out the handover of the presidency to Indonesia in Rome, Italy. The purpose of this study was to examine the reaction of the capital market on the handover of the Indonesian G20 presidency. Measurement of market reaction in this study using abnormal return proxies. The population used is all companies on the Indonesia Stock Exchange. The sampling method uses non-probability sampling with a purposive sampling technique. The samples used were 673 companies. The data analysis technique used is one sample t-test. The results of data analysis showed positive reactions occurred for five days, and negative reactions occurred for one day. The conclusion of this study is that the market reacted positively to the handover of the Indonesian G20 presidency.